Melali Ke Subak Abiansemal Storybook: Instilling the Gotong Royong Value in Grade V Elementary School Students - Dewi, Patricia Komang Ayu Asmara; Lasmawan, I Wayan; Margunayasa, I Gede (Journal for Lesson and Learning Studies, 2022)
Nowadays there is a decrease in the value of mutual cooperation that occurs in children, mutual cooperation character education needs to be improved since the elementary school level. This study aims to develop a picture story book with local Balinese wisdom to instill the value of the character of gotong royong in fifth grade elementary school students. This type of research is development research using Analysis, Design, Development, Implementation and Evaluation methods. Data collection methods using a questionnaire. The data analysis technique used quantitative and qualitative analysis. The product test subjects consisted of 2 people who were material experts, design experts, and media experts. Practitioner test of 2 teachers and 40 fifth grade elementary school students in the cluster. The results showed that the validation test reached 95.55%, at intervals of 81%-100% (very valid). The practicality test reached 98.06% at an interval of 81%-100% (very practical). The effectiveness test in the group without treatment with an average score of 66,425, while the group with treatment has an average score of 86,625. The Independent t-test shows a Sig (2-tailed) value of 0.000 (<0.05), which means there is a significant difference. Thus, the picture book with local Balinese wisdom was declared valid, practical and effective for instilling the value of the mutual cooperation character of fifth grade elementary school students. The implications of the results of developing story books on student learning outcomes can then be used as a companion to the 2013 curriculum book.